Exhibition as a media space for learning development for children in Bandung - Alba Romizal Alba; Deden Sunmedar; Elly Malihah; Rini Andriani (Jambura Journal of Educational Management, 2023)
The purpose of this study is to determine the provision of learning media space for children in the city of Bandung on the community side. The provision of learning media space for children carried out by professional event organizers (PEO) to the extent of providing learning space based on experience., Baby and kids expo is one of the events held in the city of Bandung that will provide children's experience. This research was conducted with a qualitative approach, the data obtained were based on observation data and interviews conducted with key speakers: Project Manager, Showdirector Manager, and CEO. Therefore, this research is important to be carried out as an additional material for academic science and increase knowledge of the importance of education on the community side in the packaging of exhibition events carried out to find out the role of PT. Synergy Green Production in facilitating children's learning needs is packaged at the Baby and Kids Expo and continues to consistently support learning activities for up to 25 years. The results of this baby and kids expo research provide the best service from the community side in the growth and development of children, especially children in the city of Bandung can be given space and learning development media that have been carried out by educators in schools, so space is needed so that children get experiential learning in their growth and development.